British Society of Gastroenterology endorsed guidance for the management of immune checkpoint inhibitor-induced enterocolitis. (July 2020) - Powell, Nick; Ibraheim, Hajir; Raine, Tim; Speight, Richard A; Papa, Sophie; Brain, Oliver; Green, Michael; Samaan, Mark A; Spain, Lavinia; Yousaf, Nadia; Hunter, Nikki; Eldridge, Lucy; et al.
Summary: Immune checkpoint inhibitors are a novel class of cancer treatment that have improved outcomes for a subset of cancer patients. They work by antagonising inhibitory immune pathways, thereby augmenting immune-mediated antitumour responses. However, immune activation is not cancer-specific and often results in the activation of immune cells in non-cancer tissues, resulting in off-target immune-mediated injury and organ dysfunction. Diarrhoea and gastrointestinal tract inflammation are common and sometimes serious side-effects of this type of therapy. Prompt recognition of gastrointestinal toxicity and, in many cases, rapid institution of anti-inflammatory or biologic therapy (or both) is required to reverse these complications. Management of organ-specific complications benefits from multidisciplinary input, including engagement with gastroenterologists for optimal management of immune checkpoint inhibitor-induced enterocolitis. In this British Society of Gastroenterology endorsed guidance document, we have developed a consensus framework for the investigation and management of immune checkpoint inhibitor-induced enterocolitis.